DETERMINATION OF THE CORRELATION BETWEEN NURSES' ORGANIZATIONAL COMMITMENT AND JOB-RELATED STRESS LEVELS: AN EXAMPLE OF A PUBLIC HOSPITAL - Tuğba Uluocak Köse (Rojan GÜMÜŞ, 2020)
Objective: This research was conducted in order to determine the correlation between the loyalty of nurses in Haydarpaşa Sultan Abdulhamit Han Education and Research Hospital and their job-related stress levels, which is one of the important elements of health service delivery. Method: The sample of this research consisted of military nurses who were transferred from the Turkish Armed Forces to the Ministry of Health in 2016 and 170 nurses who agreed to participate in the research at Haydarpaşa Sultan Abdulhamit Han Education and Research Hospital after the transfer and the full count method was used when calculating the sample. In the research, which was planned to be definitive, the required data was collected using the Job-related Tension Scale and the Organizational Commitment Scale. In the research, the data was collected with face-to-face interviewing method after the participants were informed of the purpose of the research and after their consent was obtained and the participants were interviewed at their convenience. The data obtained was evaluated by establishing a database in SPSS (Statistical Package for Social Sciences) 22.0 software. In the evaluation of the data, number, percentage, standard deviation and mean were used as descriptive statistical methods. Findings: According to the groups, 82 (48.2%) of the employees were previously employed at the Gülhane Military Medical Academy (GATA) and 88 (51.8%) were employees of the Ministry of Health. According to regression analysis, the total change in job-related stress level is explained by 14.9% organizational commitment total. In correlation analyses, negative correlation was found between job-related stress and emotional commitment, continuance commitment, and normative commitment. Employees who previously worked at GATA reported a significant decrease in the total value of organizational commitment relative to the total GATA value of organizational commitment. Job-related stress levels, on the other hand, showed a significant increase in employees who previously worked at GATA. Conclusion: According to the research findings, it is observed that organizational commitment tends to decrease in employees who previously worked at GATA, that there is a significant increase in job-related stress levels, and that the job-related stress of employees in GATA is high and significant. Key Words: Job-related stress, organization, organizational commitment.